2015
DOI: 10.1186/s40809-014-0001-7
|View full text |Cite
|
Sign up to set email alerts
|

Computational fluid dynamics of computed tomography angiography to detect the hemodynamic impact of intracranial atherosclerotic stenosis

Abstract: Background: In symptomatic intracranial atherosclerotic stenosis (ICAS), its hemodynamic impact may affect the risk of stroke recurrence, in addition to the degree of luminal stenosis. We therefore conducted a pilot study to evaluate the feasibility to delineate the hemodynamic impact of symptomatic ICAS lesions using computational fluid dynamics (CFD) models reconstructed based on computed tomography angiography (CTA) source images. Methods: Three-dimensional CFD models were reconstructed based on routine CTA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…16,17 We have also indicated possible prognostic values of CFD model-generated hemodynamic metrics for the risk of recurrent stroke in a small cohort of 32 patients with 70 to 99% sICAS. 16,17 We have also indicated possible prognostic values of CFD model-generated hemodynamic metrics for the risk of recurrent stroke in a small cohort of 32 patients with 70 to 99% sICAS.…”
mentioning
confidence: 91%
“…16,17 We have also indicated possible prognostic values of CFD model-generated hemodynamic metrics for the risk of recurrent stroke in a small cohort of 32 patients with 70 to 99% sICAS. 16,17 We have also indicated possible prognostic values of CFD model-generated hemodynamic metrics for the risk of recurrent stroke in a small cohort of 32 patients with 70 to 99% sICAS.…”
mentioning
confidence: 91%
“…Pressure drop across the lesion has been proposed for assessing stroke risk . Patient‐specific computational fluid dynamic (CFD) modeling was used to compute the pressure drop across stenosis . The accuracy of CFD in replicating in vivo physiological flow depends on computational strategies and modeling assumptions .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Due to the close relation between hemodynamics and the various ailments in the human body, 3 Leng et al 4 and Saho and Onishi 5 simulated hemodynamics in 3D angiography cerebral models. They studied intracranial atherosclerotic stenosis and cerebral aneurysms, respectively, but results of Saho and Onishi indicated that the cause of cerebral aneurysms remained unclear.…”
Section: Introductionmentioning
confidence: 99%